Effect of application different levels of olive mill waste water during the mechanical dismantling of the subsurface soil layer on some physical properties of this layer and on the productivity of the potato plant. - بدور رشا; جهاد ابراهيم; ربيع زينة (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out on Celtic clay soil at the Agricultural Scientific Research Center in Lattakia (Set-Kheris station) in 2019, where the study included four Treatments (T0 control without mechanical dismantling of the subsoil layer, LT0 treatment of mechanical dismantling of the subsoil layer only, T1 adding 2 L/m2 oil mill waste water during mechanical dismantling , T2 adding 4 L/m2 oil mill waste water during mechanical dismantling ), the results showed a significant decrease in bulk density after mechanical dismantling by 0.11 g/cm3 compared to the control, as it decreased in treatment T1 by 0.13 g/cm3, to decrease in treatment T2 by 0.22 g/cm3. The volume of total porosity increased after mechanical disassembly from 46.34% to 50.51%, and increased in T1 treatment to become 51.33%, reaching 54.57% in T2 treatment, and the size of air pores greater than 10 microns increased with mechanical disassembly by 5.92%, and with the addition of T1 It increased by 4.19%, to increase at the level of T2 addition by 7.88% . As for the pores that contain available water (0.2-10) microns, it increased at the level of T1 addition by 3.01% and increased at the T2 level by 3.84% compared to the control, while the smaller pores It decreased from 0.2 micron with disassembly and at the levels of addition of T1 and T2, especially at the level of addition of T2, bringing this decrease to 3.49% compared to the control. The T2 treatment was significantly superior to the rest of the treatments with regard to the average plant height (50.6 cm), the average leaf area (4483 cm2), and the average leaf surface index (2.387) compared to the control. the average production increased with dismantling only by 7.34%, and with the addition level 2 L/m2 by 13.31%, bringing this increase to 31.21% at the level of addition 4 L/m2. The percentage of dry matter increased significantly by (2%) and starch by (1.034%) in T2 treatment compared to the control